Gender Justice in Sighat Taklik Talak: Towards Equal Legal Protection for Husband and Wife in Indonesia - Amelia, Noor Izzati; Syaikhu, Syaikhu; Maulana, Anas (CV. Social Politic Genius (SIGn), 2025)
The practice of sighat taklik talak in Indonesian marriage law exclusively grants the right of pronouncement to the husband, creating an imbalance in legal protection and contradicting the constitutional principle of gender equality. This research aims to analyze the ambiguous legal position of sighat taklik talak critically and to deconstruct the gender injustice embedded within it, in order to formulate an argument for legal reform towards a reciprocal model. Employing a normative juridical research method with statutory, conceptual, and historical approaches, this study analyzes primary and secondary legal materials through systematic and teleological interpretation. The findings indicate that the legal position of sighat taklik talak is problematic. While the instrument is recognized by the Compilation of Islamic Law, it misaligns with the principle of consensualism in civil law. More fundamentally, its unilateral nature creates legally legitimized gender-based discrimination by denying an equivalent protection mechanism for the husband. It is concluded that the current practice does not reflect substantive justice. Therefore, regulatory reform of sighat taklik talak is a juridical imperative to transform it into a reciprocal protection agreement that guarantees legal certainty and equality for both husband and wife.